The clinical psychological diagnostic system (KPD-38): sensitivity to change and validity of a self-report instrument for outcome monitoring and quality assurance - Moessner, Markus; Gallas, Christine; Haug, Severin; Kordy, Hand (Clinical psychology & psychotherapy, 2011)
Background: Monitoring psychotherapeutic progress requires valid and economic measures to detect change of clinical relevance. We addressed validity and sensitivity to change of the ‘Klinisch Psychologisches Diagnosesystem 38’ (KPD-38, Clinical Psychological Diagnosis System), an instrument for outcome monitoring and quality assurance. Methods: Data from an inpatient sample (n = 1.377) were used to investigate the concurrent validity, the sensitivity to change, and the criterion validity of the KPD-38 in comparison to the Outcome Questionnaire (OQ-45) and the Brief Symptom Inventory (BSI). Results: Sensitivity-specificity analyses showed similar sensitivity and higher specificity for the KPD-38 scales compared with the BSI and OQ total scores. Change rates on the KPD-38 distress scale (DIS) were found to be lower than on the BSI (KPD-38 DIS: 36.6%, GSI: 67.7%) and the OQ-45 (KPD-38 DIS: 44.3%, OQ tot: 57.1%) total scores. Concordance was low with the BSI ([κ = 0.24] and moderate with the OQ-45 [κ = 0.45]). Discussion: Implications for applications in the field of outcome assessment and the challenge of further validation are discussed. The relation between sensitivity to change and criterion validity is highlighted. Copyright © 2010 John Wiley & Sons, Ltd. Key Practitioner Messages: • The KPD-38 is a self-report questionnaire for outcome monitoring and quality assurance, which is free of charge for research purposes. • Both OQ-45 and BSI show higher sensitivity to change than the KPD-38, overall concordance of change is moderate. • Aspects of validity should be considered in the evaluation of sensitivity to change.